EXAMINING THE IMPACT OF INDIVIDUAL AND ENVIRONMENTAL FACTORS AFFECTING UNDERGRADUATE STUDENT BURNOUT IN BANGKOK - Robkit, Achareeya; Tanyasit, Kanyarat; Sawangjaitham, Pichapa; Carrera, Mariano; Krapookthong, Maichanok (Proceedings of the International Conference on Education, 2023)
Student burnout is important, particularly in light of the COVID-19 pandemic and mandatory online learning. The purpose of this quantitative research is to examine individual factors and environmental factors affecting student burnout. And, to answer two research questions: 1) How individual factors and environmental factors are correlated to each other? 2) Which of both factors are the most important to student burnout in Bangkok? Therefore, understanding the problem would aid in preventing or mitigating student burnout. The sample group used in the study consisted of 230 undergraduate students studying in Bangkok. The researchers have used descriptive statistical analysis to analyze and process the obtained data from the online questionnaire. The result indicated that students felt more burnout over the past two years with online learning due to government restrictions. Among the six-sub factors including self-esteem, self-discipline, educational, friends, family, and school. Every sub-factor has a high level except school and education, which is a moderate level. We found that Thai undergraduates in Bangkok appear to have everything that would not cause burnout. It can be concluded that students may not know how to use the support and the abilities they have during 100% online learning, resulting in a significant level of burnout among students during the past two years. The researchers recommend that universities implement strategies such as promoting their student support structures (student-teacher mentorship), their health facilities (with online outreach) and providing physical space where students can meet safely in times of contagion. These strategies would help students reduce problems, develop healthy habits and reduce overall burnout.